Therapeutic reference range for aripiprazole in schizophrenia revised: a systematic review and metaanalysis - Hart, Xenia Marlene; Hiemke, Christoph; Eichentopf, Luzie; Lense, Xenija M.; Clement, Hans-Willi; Conca, Andreas; Faltraco, Frank; Florio, Vincenzo; Grüner, Jessica; Havemann-Reinecke, Ursula; Molden, Espen; Paulzen, Michael; et al. (Psychopharmacology, 2022)
While one of the basic axioms of pharmacology postulates that there is a relationship between the concentration and effects of a drug, the value of measuring blood levels is questioned by many clinicians. This is due to the often-missing validation of therapeutic reference ranges.
Gesehen am 18.01.2023